2017
DOI: 10.1016/j.compedu.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Teacher perceptions of the value of game-based learning in secondary education

Abstract: Teachers' perceptions of the usefulness of digital games might be a reason for the limited application of digital games in education. However, participants in most studies of teaching with digital games are teachers who do not use digital games regularly in their teaching. This study examined the practice-based perceptions of teachers who do teach with digital games -either playing or creating games -in their classroom. Semi-structured interviews were conducted with 43 secondary education teachers. Our finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
114
0
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(139 citation statements)
references
References 29 publications
6
114
0
19
Order By: Relevance
“…In addition, as the nature of the explorative case study, we were more interested in understanding the natural phenomena which occurred within the data in question and providing new research ideas for future studies to explore. However, the result of the research question three echoed the previous findings about teachers' positive perceptions of GBL when they used it in their classrooms (Huizenga, ten Dam, Voogt, & Admiraal, 2017;Watson, & Yang, 2016).…”
Section: Discussion and Implementationsupporting
confidence: 69%
See 2 more Smart Citations
“…In addition, as the nature of the explorative case study, we were more interested in understanding the natural phenomena which occurred within the data in question and providing new research ideas for future studies to explore. However, the result of the research question three echoed the previous findings about teachers' positive perceptions of GBL when they used it in their classrooms (Huizenga, ten Dam, Voogt, & Admiraal, 2017;Watson, & Yang, 2016).…”
Section: Discussion and Implementationsupporting
confidence: 69%
“…In addition, teachers' perceptions about GBL are also another barrier to overcome. According to researchers (Huizenga, ten Dam, Voogt, & Admiraal, 2017;Watson, & Yang, 2016), teachers' perceptions of the usefulness of GBL might be a reason for the limited application of digital games in education. In their study with 43 secondary teachers, Huizenga, ten Dam, Voogt and Admiraal (2017) found that most teachers who actually used games in class perceived student engagement with a game and cognitive learning outcomes as effects of the use of games in formal teaching settings.…”
Section: Impact Of Gbl On Students' Performances and Teachers' Percepmentioning
confidence: 99%
See 1 more Smart Citation
“…Machado et al (2018) state that digital games are good tools to make learners more engaged and motivated to learn. Teachers also believe that using digital games for learning can enhance learners' motivation and learning outcomes (Huizenga et al 2017). In this context, 67% of American learners learn using digital games in classrooms (Statista 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Games are excellent tools to introduce the topics and supplement lectures; such activity is much more stimulating to students than the traditional approach based on memorization (Franco-Mariscal et al, 2016). Generally, teachers report that game-based teaching motivated students to learn, then teaching with games engage students and influence their learning outcomes (Huizenga et al, 2017).…”
Section: Introductionmentioning
confidence: 99%